Successful management of bupropion poisoning: possible benefit of acidosis treatment - Altıntop, İsmail and Tatlı, Mehmet (The European Research Journal, 2017)
Bupropion is used as an antidepressant and smoking cessation aid. It has been described in the literature as a norepinephrine - dopamine reuptake inhibitor and is also a nicotinic antagonist. Bupropion itself is not a common cause of intoxication cases seen in Emergency Department (ED). The most important side effect is an increase in risk for epileptic seizures. We aimed to present the management of a 29-year-old female patient in ED with epileptic seizures and acidosis due to bupropion intoxication,who had taken 30 bupropion 150 mg tablets and 16 fluoksetin 20 mg tablets for suicidal purpose. According to her blood gas counts sodium bicarbonate therapy was begun in ED and after having response to the treatment was continued in intensive care unit. She was discharged three days later without any other seizures and complications. Although bupropion intoxication is rare it can cause severe metabolic acidosis and epileptic seizures. There is no specific antidote therapy to bupropion so symptomatic therapy still have benefit.